The Role of Renewable Energy in the Protection of the Iraqi Environment - Muna H. Ahmed, Haron H. Ahmed (Scientific Trends, 2023)
In this article, the types of renewable energies and the environmental effects of consuming these energies are studied. Energy is one of the things necessary for economic and social development and improving the quality of life, and the presence of continuous and sustainable economic energy is essential for any economic development and growth. Humankind has been aware of renewable energies such as biomass and geothermal energy for a long time and has used these energies as heat sources for shelter. With the beginning of the extraction of fossil fuels such as oil and coal and unlimited access to these products, the use of renewable energy sources, except in remote places and forest areas, has become limited and forgotten. Currently in Iraq, fossil fuels such as oil and gas are the most consumed sources of energy, and due to the limited fossil energy resources in addition to the problems caused by the consumption of these types of fuels, one must look for a place to use renewable energy and new energies for future generations. Iraq has many opportunities related to the use of rich sources of renewable and new energy such as wind energy, geothermal energy, hydroelectric energy, and solar energy. The use of these renewable energy sources not only reduces the use of limited fossil fuel resources but also prevents the harmful effects of greenhouse gases in the atmosphere and global warming. In this article, renewable and new energies such as solar energy, wind energy, geothermal energy, biomass, biogas, hydropower, and hydrogen are introduced. The technology used to harness renewable and new energies were discussed in addition to its environmental impacts, Iraq's talents, and the possibility of using these energy sources. A review of renewable and new energies shows that the development and use of renewable energies are very suitable alternatives to fossil fuels and the use of some renewable energy sources such as the sun and wind can help maintain the health of the environment.
Keywords: Energy crisis, renewable energy, environmental impacts, fossil fuels.